42 CD56-positive lymphocyte infiltration in correlation with outcome and human papilloma virus association of oropharyngeal squamous cell carcinoma. Issue 5 (May 2015) - Wagner, S.; Wittekindt, C.; Reuschenbach, M.; Hennig, B.; Thevarajah, M.; Prigge, E.-S.; Knebel Doeberitz, M. von; Dreyer, T.; Bräuninger, A.; Gattenlöhner, S.; Klußmann, J.P.
Abstract : Introduction: Tumor infiltrating lymphocytes and immune factors within the tumor microenvironment are critically related to cancer patient's prognosis. Human papillomavirus (HPV)-related oropharyngeal tumors are clinical and biological distinct from their HPV unrelated counterparts and patients with HPV relates oropharyngeal tumors display improved prognosis. We investigated possible immune cell infiltrations associated with this tumor phenotype. Material and methods: We randomly selected a cohort of 140 squamous cell carcinoma of the oropharynx (OSCC) and analyzed the presence of immune cells and HPV prevalence by immunohistochemistry and PCR followed by bead-based hybridization (Luminex technology). Cytotoxic activity of immune cells was determined by immunofluorescence double staining for representative HPV associated and HPV negative samples ( n = 20). Results: We have found significantly higher numbers of CD56+ cells in tumor ( t -test: p = 0.004) and surrounding microenvironment ( t -test: p = 0.002) in HPV associated compared to HPV negative OSCC. The prognostic value of presence of CD56+ cells was measured by Kaplan–Meier and Cox regression model analyses and correlated with a better outcome in HPV negative OSCC (Kaplan–Meier: p = 0.05) and within the entire cohort independent from HPV (Kaplan–Meier: p = 0.002; Cox regression: p = 0.046). Immunofluorescence localization of granular GZMB within CD56+ cells and coexpression of CD16 and CD56 suggests that the detected CD56+ cells mainly represent cytotoxic NK cells. Conclusion: The differential presence and distribution of cytotoxic NK-cells might be in part responsible for the improved prognosis of patients with oropharyngeal tumors and this effect is pronounced in HPV related OSCC.